MENTAL STATUS WITH SOCIAL INTERACTION CAPACITY IN THE ELDERLY AT SUKODADI COMMUNITY HEALTH CENTER, LAMONGAN DISTRICT - Umam, Khotibul; Susanto, Joko; Dewi, Tantri Tristiana; Wijayanti, Endah Sri; Fadliyah, Lailatul (Journal of Vocational Nursing, 2020)
Introduction: In the human life cycle there is growth and development either physically and mentally. In the elderly phase there are both physical and mental changes due to the degenerative process, leading to limitation in having physical activities, remembering things and speaking. This limitation affects social interaction with others which tends to decline and become passive. Decreasing social interaction of the elderly can cause the feeling of isolation, being useless and lead them to seclusion, because there is no emotional channeling through socializing. The purpose of this study was to identify the association between mental status and Social Interaction Capacity among the elderly at Sukodadi Community Health Center, Lamongan District. Methods: This quantitative study used correlational study and cross sectional design. Data were obtained from Short Portable Mental Status Questionnaire and social interaction capacity questionnaire. Samples consisted of 47 respondents, taken with consecutive sampling technique. Data analysis used Spearman test. Results: The majority of respondents (44,7%) had medium intellectual damage and the majority (51,1%) had medium social interaction capacity. The result of Spearman rho test showed p=0,024 and r=0,328 which meant that there was association between mental status and social interaction capacity at medium strength and positive correlation direction. Conclusion: There was association between mental status and social interaction capacity of the elderly at Sukodadi Community Health Center, Lamongan District.